Überlegungen zu der artistischen Prosa Gottfried Benns - Machońko, Maria (Studia Germanica Posnaniensia, 2018)
The article discusses some problems connected with the plane of meaning of Gottfried Benn's artistic prose. There is an indissoluble connection between the artistic motifs, style, technique of narration and the construction of the reflected world of the analyzed prose. It is emphasized in the article that an attempt to impose his own artistic vision of the world on the reader is the main aim of all Benn's creative manipulations.